The mathematics teachers' understanding of learning process based on 2013 curriculum 2017 revision - Ikhsan Abdul Latif; Riyadi Riyadi; Dewi Retno Sari Saputro (Intelektual Pustaka Media Utama, 2019)
This study is a qualitative research with case study strategy that aims to describe the understanding of Mathematics teacher about the learning process based on 2013 Curriculum (K13) 2017 Revision. The subjects of this study are a Mathematics teacher who has status as a Civil Servant and Honorary at SMAN 1 Wuryantoro, Wonogiri Regency. The result of this study is generally, the understanding of the two Mathematics teachers about the learning process based on K13 2017 Revision have been appropriate to the guidelines K13 2017 Revision by the Ministry of Education and Culture of Indonesia. However, the Honorary teacher's understanding of the learning process has not been appropriate to the Assessment Guidelines by Educators and the High School Education.